2018
DOI: 10.1002/tqem.21593
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of resilience and perceived health status on environmental quality of life: An oil community experience

Abstract: Research evidence on how resilience and perceived health status contributes to environmental quality of life (EQoL) in oil‐producing communities is limited. The activities of oil exploration are more likely to have an environmental impact on residents’ habitation, resulting in a lack of access to quality air, to adverse noise levels, and to poor‐quality water in households. However, evidence abounds in the literature that resilience is an important factor in sustainable development, while EQoL is significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…II. Social Support and quality of life [14] investigated the predictive role of social support and personality traits on psychological wellbeing of postpartum nursing mothers in Oyo State, Nigeria. The results showed that social support and personality traits jointly predicted the four subscales of psychological wellbeing.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…II. Social Support and quality of life [14] investigated the predictive role of social support and personality traits on psychological wellbeing of postpartum nursing mothers in Oyo State, Nigeria. The results showed that social support and personality traits jointly predicted the four subscales of psychological wellbeing.…”
Section: Review Of Related Studiesmentioning
confidence: 99%